Penerapan Model Project Based Learning untuk Meningkatkan Hasil Belajar Seni Musik Pada Pembelajaran Tematik Terpadu di Sekolah Dasar - Desyandri Desyandri; Putri Maulani (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
The implementation of the curriculum 2013 with an integrated thematic approach in the field is still not optimal and there are still many low student learning outcomes. This study aims to improve and enhance the learning outcomes of the art of music by applying the Project-Based Learning model to integrated thematic learning in elementary schools. The research method used was Classroom Action Research (CAR) with 2 (two) cycles. Data analysis was performed by taking the average results of qualitative and quantitative analyses. Data collection techniques and tools use observation, interviews, document analysis, and tests. The results showed that improvements and improvements: (1) RPP cycle I with a score of 87.28% (Good) has increased to 94.44% (Very Good); (2) the implementation of learning by teachers in the first cycle with a score of 83.33% (Good) has increased in the second cycle to 95.86% (Very Good); (3) The implementation of learning by students in the first cycle of 80.95% (Good), has increased in the second cycle to 90.48% (Very Good); and (4) the results of learning music in the first cycle obtained an average of 73.12, has increased in the second cycle to 83.67.